A Reconceptualization of Social Bond Theory to Predict Change Sequences in Offending - Mears, Daniel P. (Crime & delinquency, 2024)
We argue that reconceptualizing social bond theory (SBT) through incorporation of dual agency and change can identify unique causal change sequences, improve its ability to explain offending, and generate new questions about it. The reconceptualization recognizes that individuals and those with whom they interact play an ongoing role in contributing to the bond. It shows that changes in the bond can contribute to changes in delinquency through three sequences, each with a unique over-time pattern that depends on how bond agents respond to delinquency. We identify implications for SBT?highlighting that theoretical arguments about static effects do not necessarily equate to straightforward predictions about change effects?and, more broadly, efforts to advance theories of offending.